Employer pension plan inequality in Canada - Margaret Denton; Jennifer Plenderleith (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2010)
The purpose of this research paper is to contribute to knowledge regarding employer pension plan (EPP) inequality in Canada. Information on EPP coverage and value is analyzed using the 1999 and 2005 Surveys of Financial Security. The results indicate that women, persons who may live alone, landed immigrants, and language minorities are at a disadvantage in their EPP coverage and accrued value. In addition, age, educational attainment, occupation, industry of employment, union membership, total personal income, province, and size of urban residence figure importantly in EPP coverage. Furthermore, age, educational attainment, industry of employment, total personal income, province and size of urban residence are all-important determinants of the termination value of EPPs. To identify inequalities in EPP coverage among the sub-populations, the researchers use multivariate analysis. This allows an identification of inequalities that are not a direct result of differences in age, gender, level of education, location, or position in the labour market. Findings indicate that differences in EPP coverage for women, persons who may live alone, landed immigrants and language minorities are primarily due to differences in these other characteristics. However, the lower EPP value witnessed by these subpopulations cannot be explained by individual or labour market characteristics.
Keywords: J14; 330; employer pension plans; registered pension plans; coverage; value; inequality; seniors; landed immigrants; gender differences; minority language; Alterssicherung; Rentenpolitik; Soziale Ungleichheit; Kanada